A Rare Pattern of Acute Type A Aortic Dissection: Circumferential Intimal Invagination - von Aspern, Konstantin; Etz, Christian D.; Lehmkuhl, Lukas; Mohr, Friedrich W.; Dohmen, Pascal M. (The Thoracic and Cardiovascular Surgeon, 2012)
A 59-year-old patient with chest pain was transferred to our emergency unit. Computed tomography depicted a dissection membrane limited to the aortic root and a seemingly normal ascending aorta. Further downstream stenosis of the descending aorta appeared. Intraoperatively, complete intimal absence in the ascending aorta with intussusception into the descending aorta was evident. Ascending aortic and hemiarch replacement was performed. This rare case should raise the surgeons' awareness that preoperative imaging can differ considerably from intraoperative findings.
Keywords: acute aortic dissection; complete circumferential intimal intussusception; NIRS; aortic intimal invagination